Intrinsic-Task Motivation and Creative Writing through Project-Based Language Learning (PBLL) Using Video Scribe - Khoiriyah Khoiriyah; Utami Widiati (English Language Teaching and Research, 2020)
This paper presents the importance of intrinsic motivation to accomplish the task within project-based language learning (PBLL) using a particular technology in the form of a video scribe to elevate pre-service teachers’ creative writing. The result shows that PBLL using video scribe facilitates pre-service teachers to elevate their writing language production and their creativity exposure. The strategy also stimulates personal competence covering enthusiasm, curiosity, problem-solving, motivational intensity, intrinsic value, and patience, reasonable challenges to support student teachers’ professional competence and pedagogical competence. It also strengthens the other competence that allows them to be more sociable persons. This study implies that PBLL empowers pre-service teachers’ competencies in which the three “Hs” of Hand, Heart, and Head are embedded which allow them to encourage their creativity and critical thinking. Keywords: intrinsic task-motivation, creative writing, Project-based Language Learning (PBLL), video scribe